Capacity and Court of Protection update: some recent cases and the lessons to learn from them. Issue 5 (1st April 2016) - Baxter, Mark
Abstract : Several recent cases in the Court of Protection and the High Court have cast new light on the test for, and approach to, assessing capacity, as well the way in which expert evidence on that question will be treated. Those cases also consider the extent to which the test for capacity under the Mental Capacity Act 2005 applies in the civil courts when past transactions are impugned. The manner in which the Court of Protection will exercise its various jurisdictions to issue declarations, approve gifts from P's damages award, and appoint Deputies is also considered.